The EMU's exchange rate policy - Agnès Bénassy-Quéré; Benoît Mojon; Manfred J.M. Neumann (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1998)
Contents: 1. Forum Economique Franco-Allemand - Deutsch-Französisches Wirtschaftspolitisches Forum...1 – 2. Opening Address, Klaus Bünger...2 – 3. EMU and Transatlantic Exchange-Rate Stability - Agnès Bénassy-Quéré and Benoît Mojon...5 – 4. What Exchange Rate Policy in EMU? - Manfred J.M. Neumann...30 – 5. Summary of the Discussion...39
Keywords: 330